Mechanical and thermal properties of eco-friendly coating obtained from products of waste polyethylene terephthalate - Mirjana Jovičić; Vesna Teofilović; Jelena Pavličević; Oskar Bera; Tamara Erceg; Dragan Govedarica; Simendić Jaroslava Budinski (Zaštita Materijala)
The technology used in creating coatings is very important for the environmental science field. Regarless to the available types of raw materials, new methods of combining materials or the evolution of traditional technologies, coatings provide a range of options to meet different the range of environmental performances and appearance requirements. In this work, chemical recycling process of polyethylene terephthalate was investigated, since, the bottles grade consumption is reaching high levels, especially those of bottled water and soft drinks. Waste polyethylene terephthalate (PET) flakes were depolymerized using ethylene glycol. The resin based on waste PET was prepared from phthalic anhydride (PA), glycerin (G), ricinoleic acids and glycolyzed products of waste PET. The mechanical, thermal and chemical properties were tested. The properties of the resin based on waste PET were found to be compatible with the properties of the reference one. The synthesized resin based on waste PET could be potentially employed as the composition for the preparation of eco-friendly baking enamels.